Effects of protein intake prior to carbohydrate-restricted endurance exercise: a randomized crossover trial - Larsen, M. S.; Holm, S.; Svart, M. V.; Hjelholt, A. J.; Bengtsen, M. B.; Dollerup, O. L.; Dalgaard, L. B.; Vendelbo, M. H.; van Hall, G.; Møller, N.; Mikkelsen, U. R.; Hansen, M. (Journal of the International Society of Sports Nutrition, 2020)
Background: Deliberately training with reduced carbohydrate availability, a paradigm coined training low, has shown to promote adaptations associated with improved aerobic capacity. In this context researchers have proposed that protein may be ingested prior to training as a means to enhance the protein balance during exercise without spoiling the effect of the low carbohydrate availability. Accordingly, this is being practiced by world class athletes. However, the effect of protein intake on muscle protein metabolism during training low has not been studied.